Can the Root End Resective Surgery of Two Different Angles Affect the Apical Microleakage of the Retrofilling Material (In Vitro Study) - Ahmed Abdulkareem Mahmood; Hassanien Ahmed Al-jumaily (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Endodontic surgery become essential to save teeth when the endodontic treatments are failed.It promote root canal debridement and insertion of retrograde filling to make sure tight sealing apically.Aim: Compare the influences of two different resection angles (0 and 30 degree bevel angle to the long axisof the tooth) on the apical micro leakage by utilizing dye penetration technique.Methods: 80 single rooted permanent teeth were amputated 3 mm from the apex at two different resectionangles. Retrograde cavities were prepared and filled with Well-ROOT PT® and MTA BIOREP®. Allspecimens were immersed in 2% methylene blue dye for 24 hours. The specimens were cut longitudinallyby microtome and photographed digitally using stereomicroscope. With the use of Kinovea program dyepenetration area was measured. Two WAY Analysis of Variance (Two Way ANOVA) were used to analyzethe result statistically at P<0.05.Results: No group exhibited complete sealing of root-end zones. The group of MTA BIOREP® demonstratedstatistical significant differences with 0 degree angle which showed less leakage.Conclusion: MTA BIOREP® retro filling material with 0 degree angle of resection were significantlysuperior regarding apical microleakage compared with Well-ROOT PT®.